PEMBEKALAN PENYUSUNAN BUKU BESAR DI SMK YP IPPI PETOJO DALAM RANGKA KEGIATAN MBKM - Amalia, Dewi; Susanto, Liana (Jurnal Serina Abdimas, 2024)
The "Merdeka Belajar-Merdeka Kampus" policy was introduced in January 2020 to improve higher education in Indonesia. The program was implemented at SMK YP IPPI PETOJO in Jakarta, involving Tarumanagara University students who provided teaching assistance, specifically on service company ledger preparation. The objective was to analyze the impact of teaching assistance on student understanding and improve learning effectiveness. This program benefits students, teachers, schools, and students, with the hope of providing a sustainable positive impact in the world of education. During the three months of MBKM Teaching Assistance at SMK YP IPPI PETOJO, students as facilitators used structured steps in identifying the difficulties of class X Accounting students in understanding the preparation of service company ledgers. To overcome this problem, the author uses varied teaching methods by compiling materials such as power points, "K-pop" case studies, and Quizziz for evaluation. In addition, students also involve students in interactive interactions, and regular evaluations are carried out to improve the quality of learning at SMK YP IPPI PETOJO. The results showed a high evaluation with an average score of 4.31 out of 5, concluding that this teaching assistance was successful in increasing knowledge about the preparation of service company ledgers. The MBKM Teaching Assistance Program at SMK YP IPPI PETOJO succeeded in having a significant positive impact on class X Accounting students. High ratings of the effectiveness of teaching practice, the role of teaching assistants, and improved student understanding reflected the success of the program with an average score of 4.28 out of 5. The potential for future development and sustainability of the program was recognized, with an emphasis on diversifying teaching methods and utilizing student feedback.